2018
DOI: 10.17848/wp18-289
|View full text |Cite
|
Sign up to set email alerts
|

"But For" Percentages for Economic Development Incentives: What Percentage Estimates are Plausible Based on the Research Literature?

Abstract: This paper reviews the research literature in the United States on effects of state and local "economic development incentives." Such incentives are tax breaks or grants, provided by state or local governments to individual firms, that are intended to affect firms' decisions about business location, expansion, or job retention. Incentives' benefits versus costs depend greatly on what percentage of incented firms would not have made a particular location/expansion/retention decision "but for" the incentive. Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 10 publications
0
25
1
Order By: Relevance
“…Based on a review of studies that adopt these various methods, Bartik (2018aBartik ( , 2018b argues that the plausible range for "but for" effects is about 2%-25% with an average effect of state economic incentives at about 10%-15%, implying average deadweights of 85%-90%. However, empirical findings have varied widely, partly because of limitations of individual research designs, especially small sample sizes, and failure to account for selection bias.…”
Section: Rephannmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on a review of studies that adopt these various methods, Bartik (2018aBartik ( , 2018b argues that the plausible range for "but for" effects is about 2%-25% with an average effect of state economic incentives at about 10%-15%, implying average deadweights of 85%-90%. However, empirical findings have varied widely, partly because of limitations of individual research designs, especially small sample sizes, and failure to account for selection bias.…”
Section: Rephannmentioning
confidence: 99%
“…However, empirical findings have varied widely, partly because of limitations of individual research designs, especially small sample sizes, and failure to account for selection bias. Survey-based analyses tend to find lower deadweight effect due to suspected response biases (Bartik, 2018a).…”
Section: Rephannmentioning
confidence: 99%
See 2 more Smart Citations
“…Though incentives are highly prevalent, the literature shows substantial doubt regarding whether they alter firm decisions. Bartik (2018) reviews studies investigating decisions and concludes that incentives infrequently alter firm decisions (2% to 25%). A poll of CEOs in North Carolina revealed that talent was the biggest driver of location decisions, with 30% not aware that their firm had received cost-based assistance (Jolley, Lancaster, & Gao, 2015).…”
Section: Literature Debate Surrounding Place Promotionmentioning
confidence: 99%